Ectopic Ureteral Insertion into the Seminal Vesicle Causing Recurrent Epididymitis in a 24-Year-Old - Boswell, Timothy Charles (J Endourol Case Rep, 2015)
A 24-year-old male was found to have recurrent epididymitis secondary to ectopic ureteral insertion to the seminal vesicle. His ipsilateral kidney was atrophic and ectopic in the pelvis, suggesting a complex failure of embryological development. He was successfully treated with robot-assisted laparoscopic nephroureterectomy.